2005
DOI: 10.4315/0362-028x-68.9.1884
|View full text |Cite
|
Sign up to set email alerts
|

Consumer Food Safety Knowledge, Practices, and Demographic Differences: Findings from a Meta-Analysis

Abstract: Risk communication and consumer education to promote safer handling of food can be the best way of managing the risk of foodborne illness at the consumer end of the food chain. Thus, an understanding of the overall status of food handling knowledge and practices is needed. Although traditional qualitative reviews can be used for combining information from several studies on specific food handling behaviors, a structured approach of meta-analysis can be more advantageous in a holistic assessment. We combined fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

20
162
3
4

Year Published

2009
2009
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 209 publications
(189 citation statements)
references
References 27 publications
20
162
3
4
Order By: Relevance
“…Overall, studies on food safety are inconsistent with regard to the relationship between risk perception and age (Klontz, Timbo, Fein, & Levy, 1995). Moreover, our findings are consistent with those of other studies, in which lower education levels were reported to be associated with safer food handling behaviours (Altekruse, Yang, Timbo, & Angulo, 1999;Medeiros, Hillers, Kendall, & Mason, 2001;Patil, Cates, & Morales, 2005).…”
Section: Discussionsupporting
confidence: 83%
“…Overall, studies on food safety are inconsistent with regard to the relationship between risk perception and age (Klontz, Timbo, Fein, & Levy, 1995). Moreover, our findings are consistent with those of other studies, in which lower education levels were reported to be associated with safer food handling behaviours (Altekruse, Yang, Timbo, & Angulo, 1999;Medeiros, Hillers, Kendall, & Mason, 2001;Patil, Cates, & Morales, 2005).…”
Section: Discussionsupporting
confidence: 83%
“…It was apparent that food safety training was not adequately provided to volunteers who are members of the general public. Previous studies showed inadequate food handling practices for the general public (Kwon, Wilson, Bednar, & Kennon, 2008;Patil et al, 2005;Redmond & Griffith, 2003). Therefore, the lack of food safety training may present an increased risk for foodborne illness for a large group of people served at these volunteer-run operations.…”
Section: Identified Food Safety Risksmentioning
confidence: 99%
“…Personal hygiene is one of the major challenging areas in consumer food handling practices (Patil et al, 2005;Redmond & Griffith, 2003) and potential contamination by consumers may be further increased by utilizing self-service and family-style service options, which were frequently used by our participants (n = 57, 41.3%). A case study conducted by Dippold and co-authors (2003) showed that a lack of sneeze guards at the buffet line, which act as a barrier between individuals and the food served, could have contributed to an outbreak of gastroenteritis.…”
Section: Tablementioning
confidence: 99%
See 1 more Smart Citation
“…Income, age, race, and gender are commonly collected demographics that could predict behavior characteristics. Thus far, studies have found male consumers to be less aware of food safety practices and that high income does not necessarily predict knowledge of food safety practices (9).…”
Section: Introductionmentioning
confidence: 99%